The effects of active video games on physical activity among overweight and obese adolescents: a systematic review - Soh, Kim Geok; Mai, Yiqiang; Saad, Hazizi Abu; Qi, Fengmeng (Human Resource Management Academic Research, 2024)
Purpose: This systematic review aimed to examine the effects of active video games (AVGs) on physical activity (PA) among overweight and obese adolescents while considering the physical, psychological, and physiological determinants that may influence PA within diverse settings. The primary objective was to ascertain the effectiveness of AVGs in promoting PA among this specific population. Method: The Preferred Reporting Items for Systematic Reviews and Meta-Analyzes Statement guidelines were used to search the PubMed, SCOPUS, EBSCOhost (SPORTDiscus), and Web of Science databases for studies published in the last 10 years (2011–2021). Keywords related to physical activity, being overweight or obese, and teens were used. From the 833 studies, 15 fulfilled all eligibility criteria and were included in this review. Results: The study results revealed that AVGs could effectively reduce sedentary behaviour and screen time. However, the results of PA, moderate-to-vigorous physical activity (MVPA), and relevant physiological variables (e.g., energy expenditure, VO2max) are still unclear because of design problems, measurement issues, and other methodology concerns. However, the results of psychological variables (e.g., self-efficacy towards PA, intrinsic motivation) affecting PA are clear, and AVGs can effectively improve the psychology of participants. Conclusion: Findings confirmed AVGs as a promising addition to promoting PA and health. Though it may not be wise to use it alone as the ultimate means to achieve the goal, it may have an ideal effect if other elements are integrated, such as the participation of peers or parents, or combined with traditional exercise.